On the time varying mitigation performance of reflective geoengineering technologies in cities. (January 2018) - Lontorfos, V.; Efthymiou, C.; Santamouris, M.
Abstract: Cities face important overheating problems caused by the local and global climate change. Detailed mitigation and adaptation plans and strategies, are designed and applied to counterbalance the impact of the overheating challenges. Albedo management seems to be among the more considered mitigation strategies. A barrier to the wider use of reflecting technologies is the lack of quantitative experimental data and concrete knowledge about their mitigation contribution. Up to now, the performance of the reflective mitigation technologies is assessed based on simulation results considering the initial optical properties of the materials and neglecting ageing and weatherization phenomena. The article present information on the global performance of reflecting mitigation technologies, as measured in a large scale urban mitigation project employing several types of reflecting technologies. It is shown, that because of the weatherization effects, the mitigation potential of the materials is reduced, during the first year after their installation, by at least, 25%. Despite the ageing effects, reflective pavements have found to contribute in reducing the peak summer ambient temperature up to 1, 7 K, while their surface temperature was up to 12, 3 K lower than that of conventional pavement reducing considerably the sensible heat released to the atmosphere. Highlights: Weatherization affects the mitigation potential of the reflective materials at least, 25%. Reflective pavements contribute in reducing the peak summer ambient temperature up to 1, 7 K. Surface temperature of reflective pavements was up to 12, 3 K lower than that of conventional pavement.